Preliminary Study of a Web-based Tool for Enhancing the Informed Consent Process in Schizophrenia Research - Harmell, Alexandrea L. (2012)
Printed research consent forms serve to legally document what has been disclosed, but are usually suboptimal as a means of actually communicating that information to potential participants. We conducted a preliminary study of web-based multimedia consent. Participants included 19 patients with schizophrenia and 16 normal comparison (NC) subjects randomly assigned to a routine or web-media consent. Although comprehension among NCs was excellent regardless of consent condition, the web-based consent was associated with better comprehension and satisfaction among patients with schizophrenia. Findings suggest web-aided multimedia consent is feasible and potentially more effective than printed consent forms in schizophrenia research.